ANALISIS PERSEDIAAN BAHAN BAKU PADA INDUSTRI TAHU “VIVI” DI KOTA PALU - Tarima, Siti Rahma A.; Mappatoba, Marhawati; Laapo, Alimuddin (AGROTEKBIS, 2018)
This study aims to determine the amount of economic order, reordering, the amount of safety stock, and the total cost ofsafety stock.Research conducted at Buah Pala St. No. 12 BoyaogeVillage, Tatanga subdistrict, Palu Central Sulawesi in April to May 2016.Respondents were drawn in the study consisted of 3 persons namely 1 leader, 1 employee production, and 1 parts warehousing.The analysis used is EOQ, safety stock, reordering, and total cost of raw materials.The results showed the number of purchasesfor EOQ economical soybeans raw material in Industry Tofu